Application of Criminal Offenders Misuse of National Identification Numbers for Phone Card Registration in Makassar City - Sri Buyung; Marilang; Kahfi, Ashabul (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
The research aims to investigate the protection of privacy rights for SIM card users under the registration system and identify obstacles faced by individuals misusing others' National Identification Numbers (NIK) without consent. This study employs a combination of normative legal research and empirical legal research, focusing on telecommunications businesses in Makassar City, South Sulawesi Province. Data collection involves primary and secondary sources. The findings indicate that despite the absence of specific laws on starter pack registration, Indonesian citizens are protected by constitutional, administrative, ITE (Information and Electronic Transactions), and personal data protection laws. However, obstacles exist in enforcing criminal offenses related to NIK misuse, including outlet registration by actors lacking buyer identities due to fierce competition and public preference for instant solutions without considering the consequences of using others' NIK for SIM card registration.